2008
DOI: 10.1002/gps.2161
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to perceived quality of life in patients with Alzheimer's disease: the patient's perception compared with that of caregivers

Abstract: Aims: To compare care recipient and caregiver perceptions of quality of life in patients (QoLp) with Alzheimer's disease (AD). To identify associated factors, and the concordancesdiscrepancies. Method:Cross-sectional analytic study of 236 patients and their carers using the Quality of Life in Alzheimer's Disease (QoL-AD) scale, socio-demographic data and clinical examination. Results:Patients scored the QoL-AD more favourably than did caregivers (34.4 vs. 31.3, p<0.001). Cognitive deterioration did not affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
169
3
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(216 citation statements)
references
References 31 publications
33
169
3
11
Order By: Relevance
“…Both groups had heterogeneous QoL scores, which led to a non-significant result. These results corroborate the results in the literature, which stress the inverse association between caregiver burden 18,19 and depressive symptoms 20,21 and QoL of caregivers. It has been suggested that caregivers' subjective experiences of depression and burden were more predictive of caregivers' QoL than the objective PwD-related variables, such as the PwD cognitive impairment or functional abilities 20 .…”
Section: Discussionsupporting
confidence: 91%
“…Both groups had heterogeneous QoL scores, which led to a non-significant result. These results corroborate the results in the literature, which stress the inverse association between caregiver burden 18,19 and depressive symptoms 20,21 and QoL of caregivers. It has been suggested that caregivers' subjective experiences of depression and burden were more predictive of caregivers' QoL than the objective PwD-related variables, such as the PwD cognitive impairment or functional abilities 20 .…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, Argüelles et al (2001) showed that caregiver depression but not burden was related to caregiver rating bias. For quality of life, the domain with the most numerous and most current studies, the consensus is that caregiver burden is a strong predictor of dyadic rating discrepancy (Karlawish et al, 2001;Sands et al, 2004;Conde-Sala et al, 2008;Schulz et al, 2013). Caregiver depression, however, has been seen as tending to play a less significant role in the dyadic rating discrepancy of quality of life (Karlawish et al, 2001;Schulz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(AD) This research has shown that in patients higher depression scores, (2-4) the presence of behavioral disorders (5-7) and greater functional deficits (8,9) all have negative effects on QoLp. Among caregivers, poorer ratings of QoLp have been shown to be associated with functional deficits (10,11) and behavioral disorders (3,9) in the patient and with burden (3) and depression (12,13) in the caregiver. Some authors have also reported that perceptions of QoLp are affected by sociodemographic and contextual factors such as the caregiver's gender (14), his or her relationship to the patient, (15)(16)(17)) the patient's place of residence (2,3) or the environmental conditions.…”
mentioning
confidence: 99%
“…(18) Although the assessment of QoLp may be a valid and reliable indicator at any stage of the disease there are certain aspects which require careful consideration. One of the most important in this regard concerns the large discrepancy between patient and caregiver reports of quality of life, (3,19) this being particularly notable as the severity of dementia increases; (12)(13)(14)(15)(16)(17)(18)(19)(20) other factors to consider in this regard are the influence of depression (21) and reduced awareness of deficits (anosognosia) in the patient. (22)(23)(24)(25)(26) In light of the above the aims of the present study were as follows: 1) to determine the influence of severity of dementia, depression and anosognosia as regards the discrepancies between patient and caregiver reports of QoLp; and 2) to identify specific groups of patients associated with these discrepancies.…”
mentioning
confidence: 99%